A crítica da moral e a transvaloração dos valores em Nietzsche: uma possibilidade para a formação de um indivíduo além-da-moral - Santos, Vani Letícia Fonseca dos (2010)
This dissertation is an analysis about the critical moral done by Nietzsche, with the same condition for the revaluation of values moral, and consequently the possibility of finding that process the formation of a new type of individual - the man of the future. We will analyze the origin of moral values, how the they have been altered throughout history, exemplifying the problem of "good" and "evil." Address the issue of truth, through the where the creations of values and theories are now treated as "discoveries" by giving them greater notoriety and "value". In that sense, it is necessary to investigate the consequences of the opposition between moral of the master and of the slave - the first example of a posture proud and affirming, while the latter shows up as a reflection of and weak individuals who deny the conflict and therefore the Mr values: life. Here Nietzsche tells us that his "esteem" formoral of the Lord is one of the access roads to his new conception of man and recovery of another moral posture, which opposes the tradition coined by christian values. The german philosopher sought in identification of prominent individuals, those capable of not only understand their philosophy, but also to undertake the proposed transition with the revaluation of moral values. Finally, we will address the theme about the notion of will power as a condition for a new type the individual who identifies with them and who assumes the task of creation of new values. Our work seeks to establish the need for genealogical critique of Nietzsche values for formation of its proposal for revaluation, seeking a new form of conceive of morality as well as the importance of this process for a new individual, in addition to traditional morality.